The functional interplay of lncRNA EGOT and HuR regulates hypoxia‐induced autophagy in renal tubular cells - Wang, I‐Kuan; Palanisamy, Kalaiselvi; Sun, Kuo‐Ting; Yu, Shao‐Hua; Yu, Tung‐Min; Li, Ching‐Hao; Lin, Feng‐Yen; Chou, An‐Kuo; Wang, Guei‐Jane; Chen, Kuen‐Bao; Li, Chi‐Yuan (Journal of cellular biochemistry, 2020)
Autophagy, an important cellular homeostatic mechanism regulates cell survival under stress and protects against acute kidney injury. However, the role of long noncoding RNA (lncRNA) in autophagy regulation in renal tubular cells (HK‐2) is unclear. The study was aimed to understand the importance of lncRNA in hypoxia‐induced autophagy in HK‐2 cells. LncRNA eosinophil granule ontogeny transcript (EGOT) was identified as autophagy‐associated lncRNA under hypoxia. The lncRNA EGOT expression was significantly downregulated in renal tubular cells during hypoxia‐induced autophagy. Gain‐ and loss‐of‐EGOT functional studies revealed that EGOT overexpression reduced autophagy by downregulation of ATG7, ATG16L1, LC3II expressions and LC 3 puncta while EGOT knockdown reversed the suppression of autophagy. Importantly, RNA‐binding protein, (ELAVL1)/Hu antigen R (HuR) binds and stabilizes the EGOT expression under normoxia and ATG7/16L1 expressions under hypoxia. Furthermore, HuR mediated stabilization of ATG7/16L1 expressions under hypoxia causes a decline in EGOT levels and thereby promotes autophagy. Altogether, the study first reveals the functional interplay of lncRNA EGOT and HuR on the posttranscriptional regulation of the ATG7/16L1 expressions. Thus, the HuR/EGOT/ATG7/16L1 axis is crucial for hypoxia‐induced autophagy in renal tubular cells. The findings show the interplay of lncRNA EGOT and HuR on the post‐transcriptional regulation of ATG7/16L1 expressions. HuR‐mediated differential stabilization of lncRNA EGOT and ATG7/16L1 controls hypoxia‐induced autophagic response in renal tubular cells.